La dimension temporelle spécifique de l’aide spécialisée aux élèves en difficulté - Christine Pierrisnard (Recherches en Éducation)
Pedagogical way of specialized help to pupils with learning difficulties, provided par RASED, differs from other types of assistance, provided by regular teachers, and articulates to it. The research seeks to identify the continuities and ruptures that occur, particularly in terms of temporal dimension in the teaching practices and activities for pupils, and help build the profession of specialized teacher “E” its specificity. The corpus analysis reveals few tracks of interest to the teacher training to better understand how can co-develop an aid to conceptualization of representations most appropriate time for all actors in the didactic system, specifically in a dialectic between continuity and rupture.